2007
DOI: 10.2143/ac.62.4.2022277
|View full text |Cite
|
Sign up to set email alerts
|

QTc dispersion on the baseline ECG predicts arrhythmias during electroconvulsive therapy.

Abstract: We conclude that QTc dispersion appears to be a valid predictor of arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…This is also in line with the finding that QTd was increased in children with epilepsy regardless of AED treatment (Akalin et al., 2003). Pathologic QTd was also shown to predict cardiac arrhythmias during electroconvulsive therapy (Rasmussen et al., 2007), but we did not observe a significant association between arrhythmias and pathologic QTd (mixed logistic regression model, p = 0.571).…”
Section: Discussioncontrasting
confidence: 76%
“…This is also in line with the finding that QTd was increased in children with epilepsy regardless of AED treatment (Akalin et al., 2003). Pathologic QTd was also shown to predict cardiac arrhythmias during electroconvulsive therapy (Rasmussen et al., 2007), but we did not observe a significant association between arrhythmias and pathologic QTd (mixed logistic regression model, p = 0.571).…”
Section: Discussioncontrasting
confidence: 76%
“…In apparently healthy populations, QTd >50 ms (or >60 ms) is considered abnormal, indicating an increased risk for tachyarrhythmia (Zaidi et al, 1997;Macfarlane et al, 1998). Pathologic QTd also seems to predict arrhythmias (mainly premature atrial and ventricular contractions) with electroconvulsive therapy (Rasmussen et al, 2007). Therefore, seizure activity in the presence of pathologic QTd could favor the onset of cardiac arrhythmia.…”
Section: Qt Dispersionmentioning
confidence: 99%
“…Tricyclic antidepressants are known to induce prolongation of the QT interval. Rasmussen et al 24 reported that QTcD as measured on the baseline ECG positively correlated with number of arrhythmias during ECT. 22,23 The baseline values of the QTD and QTcD in 90% of patients were also higher than the upper normal limits of 50 milliseconds.…”
Section: Discussionmentioning
confidence: 99%